Criminal Liability of Passive Money Laundering Perpetrators: Analysis of Decision Number 626/PIDSUS/2020/PN JKT.SEL - Saeful Bahari, Bayu; Priyatno, Dwidja; Handayani, Trini; Rusman (Yayasan Studi Cendekia Indonesia (YSCI), 2025)
Criminal liability for perpetrators of passive money laundering, with a focus on the analysis of Decision Number 626/PIDSUS/2020/PN JKT.SEL. Passive money laundering refers to actions that are not directly related to the main crime but still play an important role in disguising the origin of the proceeds of crime. This study uses a normative legal method, with analysis of legislation, court decisions, and related legal literature. Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes is the main legal basis for regulating money laundering, both active and passive. Article 5 paragraph (1) of this law stipulates that perpetrators of passive money laundering can be subject to criminal sanctions if they are proven to have received, controlled, or used assets that are known or reasonably suspected to be derived from criminal acts. In addition, the system of evidence in money laundering cases applies the principle of reverse burden of proof, whereby the defendant must prove that their assets are not the proceeds of crime. In the case analysed, the Panel of Judges ruled that the defendant was legally and convincingly proven to have committed the passive money laundering crime by trading accounts and using those accounts for illegal transactions, including online gambling. This ruling emphasises the importance of strict law enforcement in dealing with passive money laundering crimes to support effective prevention and law enforcement efforts in Indonesia.